2003
DOI: 10.1097/00002371-200303000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Evaluation of Humanized Anti-Epidermal Growth Factor Receptor, Monoclonal Antibody h-R3, in Patients With Advanced Epithelial-Derived Cancer

Abstract: Epidermal growth factor receptor (EGFR) overexpression has been detected in many tumors of epithelial origin, and it is often associated with tumor growth advantages and poor prognosis. h-R3 is a genetically engineered humanized antibody (mAb) that recognizes an epitope located in the extracellular domain of human EGFR. The antibody exhibited potent in vitro and in vivo antitumor effect on EGFR overexpressing cell lines. To study safety, pharmacokinetics, and biodistribution, 12 patients with advanced epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 36 publications
3
77
1
Order By: Relevance
“…13 Nimotuzumab has shown a synergic effect when combined with external bean radiotherapy and it has been well tolerated through the intravenous route for treating the advanced epithelial-derived cancer patients including high-grade glioma patients. [14][15][16][17] Recent data from a phase I/II clinical trial, with 200 mg/week of Nimotuzumab for 6 weeks, administered by IV infusion, combined with external radiotherapy in 24 patients with high grade astrocytoma showed no grade 3/4 adverse events. Four patients achieved complete response, 5 a partial response and 11 stable disease, while the median survival time was 22.17 months for all subjects.…”
Section: Introductionmentioning
confidence: 99%
“…13 Nimotuzumab has shown a synergic effect when combined with external bean radiotherapy and it has been well tolerated through the intravenous route for treating the advanced epithelial-derived cancer patients including high-grade glioma patients. [14][15][16][17] Recent data from a phase I/II clinical trial, with 200 mg/week of Nimotuzumab for 6 weeks, administered by IV infusion, combined with external radiotherapy in 24 patients with high grade astrocytoma showed no grade 3/4 adverse events. Four patients achieved complete response, 5 a partial response and 11 stable disease, while the median survival time was 22.17 months for all subjects.…”
Section: Introductionmentioning
confidence: 99%
“…In a preclinical study, nimotuzumab showed marked antiproliferative, proapoptotic, and antiangiogenic effects in tumours that overexpress EGFR (Crombet-Ramos et al, 2002). In early clinical trials, nimotuzumab has shown a longer half-life and a greater area under the curve (AUC) in comparison with other anti-EGFR antibodies (Crombet et al, 2003). A phase I/II trial showed that nimotuzumab was well tolerated and enhanced the curative potential of radiation in patients with advanced head and neck cancer (Crombet et al, 2004).…”
mentioning
confidence: 99%
“…Developed in the early 2000s, nimotuzumab (a humanized IgG1 mAb also known as h-R3) soon demonstrated consistent in vitro and in vivo anticancer properties, 60 boosting an intense wave of clinical test, often relying on the combination of nimotuzumab with radiotherapy. [61][62][63][64] In parallel, nimotuzumab was conjugated to radionuclides including 188 Os, 99 mTc, 188 Re and 177 Lu, and some of the resulting immunoradioconjugates entered clinical tests as diagnostic or therapeutic tools for tumors of epidermal origin. [65][66][67][68] Now, approximately 20 phase I-II clinical studies are investigating the efficacy of nimotuzumab for indications as diverse as glioma, head and neck, colorectal and lung cancer.…”
Section: Monoclonal Antibodies Under Advanced (Phase Iii-iv) Clinicalmentioning
confidence: 99%